Cardoon cake as a sustainable alternative ingredient in broiler feeding - Federica Mannelli; Federica Scicutella; Giuseppe Conte; Matteo Daghio; Carlo Viti; Ilaria Galigani; Elisabetta Toni; Alessandra Miele; Giovanni Brajon; Lapo Nannucci; Arianna Buccioni (Italian Journal of Animal Science)
A strategy to improve poultry meat production sustainability is the use of by-products from agro-industries, such as cardoon cake (CC). Due to limited literature available, this trial aimed to study the effect of CC as an alternative protein source to soybean meal (SM) or insect meal (black soldier fly, Hermaetia illucens) on broilers’ performance, welfare, and meat quality. Eighty day-old chickens were allocated into 4 dietary treatments composed of 5 replicated pens (4 animals per pen): control group (C) fed a basal diet with SM as main protein source; HI15 group fed C with 15% of SM replaced with H. illucens meal; CC15 group fed C with 15% SM replaced with CC; CC20 group fed C with 20% of SM replaced with CC. In the starter period, chicks from CC15 showed similar trends in weight gain (WG), feed intake (FI), and feed conversion ratio (FCR) to the C group; FCR was also comparable to that in HI15, but FI was lower with respect to HI15. In the finisher period, WG in CC15 and CC20 groups did not differ from the C and HI15 groups, but the FCR worsened with respect to C whilst remaining comparable to HI15. The meat fatty acid profile from animals fed CC was rich in oleic acid. Bifidobacterium was detected in the CC20 group only, which also showed significantly lower relative abundance of Bacteroides, Monoglobus, UCG-009, Colidextribacter, and NK4A214_group, and significantly higher relative abundance of Latilactobacillus. These results show that CC can be used for broilers feeding.